VARIASI GENETIK SERANGGA PENGHASIL SUTERA EMAS Cricula trifenestrata Helf. (LEPIDOPTERA : SATURNIIDAE) BERDASARKAN PENANDA RAPD (Random Amplified Polymorphic DNA) - , Karlina Purbasari, S.Si, Dr. Niken Satuti Nur Handayani, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Cricula trifenestrata is one of the wild silkworms to be first grown in Daerah Istimewa Yogyakarta (DIY) in 1995. C. trifenestrata is in the family of Saturniidae with a special trait of its ability to produce golden cocoon. The wide distribution of C. trifenestrata causes diversity. However, the study of genetic diversity of C. trifenestrata has not been discovered yet. This study is aimed to discover the genetic variation of C. trifenestrata on five locations in DIY and two other locations in Central Java based on RAPD molecular marker, to support and give clear classification. The morphological characters were observed according to the color of wings, the body size, and the wide spread of wings. Genetic variation was observed by using four RAPD primers (OPA-01, OPA-02, OPA-11, OPA-20). The amplification result is visualized through electrophoresis and the ribbon appeared was converted into binary data to determine the percentage of polymorphic of C. trifenestrata. Cluster analysis was done by using a method called Unweighted Pair-Group Methods Using Arithmatic Averages (UPGMA) NTSys-PC. The result of this study showed that the morphology of C. trifenestrata are diverse. Genetic variation in each location is stated in polymorphic percentage, i.e. Magelang (95,52%), Dlingo (93,75%), Playen (90,38%), Ngawen (88,89%), Karang Tengah (83,82%), Wonogiri (83,02%) and Pakem (72,09%). Amplification with four RAPD primers produce 101 polymorphic loccus and 1 monomorphic loccus with OPA-20 primer at 750 bp. C. trifenestrata from seven locations of this research were classified into two main dendogram cluster at similarity value of 0.65 (65%) and the majority of the species was clustered in one group with a similarity of 0.67 (67%). C. trifenestrata from avocado with percentage of polymorphic between 72-95%, from Spondias dulcis (kedondong) with percentage of polymorphic between 90-93% and from cashew with percentage of polymorphic between 83-88%.